2021
DOI: 10.3390/antiox10121887
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Folinic Acid Administration on Lower Limb Ischemia/Reperfusion Injury in Rats

Abstract: Surgery under ischemic conditions, lasting up to 3 h, is routinely performed in orthopedic surgery, causing undesirable injury due to ischemia-reperfusion syndrome, with short and medium-term functional repercussions. To date, there is no established prophylactic treatment. In this work we evaluated folinic acid (FA) in a rodent model of lower limb ischemia-reperfusion (IRI-LL). 36 male WAG rats underwent 3 h of lower limb ischemia. In the saline group, rats received intraperitoneal administration of saline (u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 55 publications
2
13
0
Order By: Relevance
“…Relevant studies have shown that lumbar discectomy and bone graft fusion and internal fixation can effectively mitigate the pain in patients with lumbar disc herniation. It also features low trauma, fast recovery, and simple operation [ 4 ], which makes the surgical method widely favored by patients and physicians. However, due to the lack of understanding of the knowledge of their own diseases in most patients, patients are prone to resistance to treatment, and it greatly compromises the effect of the operation [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Relevant studies have shown that lumbar discectomy and bone graft fusion and internal fixation can effectively mitigate the pain in patients with lumbar disc herniation. It also features low trauma, fast recovery, and simple operation [ 4 ], which makes the surgical method widely favored by patients and physicians. However, due to the lack of understanding of the knowledge of their own diseases in most patients, patients are prone to resistance to treatment, and it greatly compromises the effect of the operation [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the response of the rat musculature to ischemia-reperfusion-related events can be compared to the damage caused in humans. These studies, carried out on young adults (3–4 months), confirmed the efficacy of our device in inducing and maintaining controlled ischemia [ 51 ], as well as the usefulness of FA as a prophylactic treatment for reducing IRI-LL [ 52 ].…”
Section: Discussionmentioning
confidence: 52%
“…The functional recovery after IRI-LL was assessed using a rotarod apparatus (Panlab Harvard Apparatus, Barcelona, Spain). The rotation speed and acceleration, as well as the time for acclimatization to the rod, were the same as those indicated in previous works of our group [ 51 , 52 ]. The latency time to fall, as well as the speed of the rod at the time of the fall, were automatically recorded using the SeDaCom v2.0.03 software (Panlab Harvard Apparatus, Barcelona, Spain).…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…Blood flow restoration triggers a sequence of biochemical processes, such as the formation of reactive oxygen species (ROS), the activation of cytokines, and the alteration of capillary permeability; this process exacerbates the cellular dysfunction suffered during the ischemic process, being the most affected tissue in the extremities. Cearra and colleagues [2] evaluated the effectiveness of folinic acid in a rodent model of lower-limb ischemia-reperfusion, emulating the characteristics, the techniques, and the duration of ischemia periods used in clinical practice when performing limb surgery under ischemic conditions. The authors concluded that the administration of folinic acid before tourniquet release could be considered a prophylactic treatment to prevent IR-induced damage.…”
mentioning
confidence: 99%